Children in Out of Home Care: Should we give them a Fair Go?. (8th December 2015) - Peel, Nicole; Beckley, Alan
Abstract : This paper identifies a sizeable group of vulnerable children who suffer discrimination and under-achievement on a daily basis in Australia, with particular attention to NSW out-of-home care (OOHC) practices. The purpose of the paper is to highlight the gaps in services specifically relating to the education of children in OOHC, care leavers and young carers. The paper identifies the extent of the issue, the ways that OOHC children suffer discrimination and possible solutions. As OOHC children are not a specific equity group targeted for support by governments, their identity, numbers, problems and issues are not recorded or singled out for specialist support. The paper recognises that further research is required, but offers some ways forward giving examples of widening participation in education. However, it comes to the conclusion that OOHC children are not given a "Fair go".